4D Printed Shape Morphing Biocompatible Materials Based on Anisotropic Ferromagnetic Nanoparticles. (11th June 2022) - Kuhnt, Tobias; Camarero‐Espinosa, Sandra; Takhsha Ghahfarokhi, Milad; Arreguín, Mariana; Cabassi, Riccardo; Albertini, Franca; Nieto, Daniel; Baker, Matthew B.; Moroni, Lorenzo
Abstract: Shape morphing materials, especially those fabricated by 4D printing, are gaining much attention due to their versatility of actuation and capability of being programmed in advance. These materials become particularly interesting for biomedical applications where implant materials could be remotely actuated, exerting a force on the surrounding tissues and cells. However, applications in this field have been restricted due to the biocompatibility of the materials and the character of the required stimuli, generally not compatible with physiological environments. Magnetic nanoparticles (MNPs) represent a great opportunity to this end; however, the actuation results in a uniform movement toward the magnet that requires anchoring of the object. Here, for the first time, the application of anisotropic Fe3 O4 MNPs is described, and synthesized by a novel and easy route, that can be aligned on pre‐defined patterns within objects printed by digital light processing, resulting in materials that can be actuated remotely (4D printing). These nanoparticles (178 nm × 55 nm), show good biocompatibility when directly seeded on top of human mesenchymal stem cells, despite being uptaken. Most importantly, the alignment of the MNPs can tune the movement of fabricated nanocomposite materials, resulting in complex movements of attraction or repulsion depending on the direction of the applied magnetic field. Abstract : 4D printed materials based on magnetic nanoparticles allow remote and reversible actuation of pre‐defined structures. However, the fabrication of nanocomposites results in structures that move uniformly toward the magnetic field and require the anchoring of the material. Here, anisotropic nanomagnets are synthesized to create 4D printed biocompatible materials that can be actuated remotely by predefined anisotropic patterns of attraction and repulsion.